Biographical Sketch: Harald Tscherne, MD (1933–Present) - Brand, Richard A. (Springer US, 2013)
This biographical sketch on Prof. Harald Tscherne corresponds to the historic text, The Classic: Der Straßenunfall [Traffic Accidents]. Wien Med Wochenschr. 1966;116:105–108 (Translated by Dr. Roman Pfeifer), available at DOI 10.1007/s11999-013-3012-9.